2016
DOI: 10.1007/s11249-016-0738-z
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Slide–Roll Ratio on ZDDP Tribofilm Formation

Abstract: The anti-wear performance and action mechanisms of zinc dithiophosphate (ZDDP) have been investigated under various test conditions. The Mini Traction Machine-Space Layer Imaging (MTM-SLIM) is a widely used and useful method for monitoring tribofilm formation by ZDDPs. However, tests are generally carried out in mixed sliding-rolling conditions, typically between 50 % SRR (slide-roll ratio) and 100 % SRR. In this paper, the authors describe an investigation of ZDDP film formation at SRRs much higher than 100 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 18 publications
3
31
0
Order By: Relevance
“…(Some results were obtained in previous research [21].) Figures 3 and 4 show interference images on the MTM steel balls at 5 and 20 N, respectively, while Fig.…”
Section: Mtm-slim Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…(Some results were obtained in previous research [21].) Figures 3 and 4 show interference images on the MTM steel balls at 5 and 20 N, respectively, while Fig.…”
Section: Mtm-slim Resultssupporting
confidence: 56%
“…The mini traction machine-space layer imaging (MTM-SLIM), PCS Instrument is a well-known and useful method to monitor ZDDP tribofilm growth in situ, and its use to study the kinetics of ZDDP tribofilm growth has been reported widely [11][12][13][14][15][16][17][18][19][20][21][22]. In this paper, MTM-SLIM has been used to monitor ZDDP tribofilm formation and wear on the ferrous counter-surface rubbed against Al-Si alloys.…”
Section: Introductionmentioning
confidence: 99%
“…It is of interest to compare the behaviour seen in reciprocating sliding with that seen and reported previously in unidirectional sliding conditions [23]. As shown in Fig.…”
Section: Comparison With Results In Unidirectional Purementioning
confidence: 68%
“…From the previous research by the authors (Figs. 13,14) in [23], in the unidirectional pure sliding conditions shown in Fig. 4, after 30 s from the beginning of the test, 550-nm-thick particles were observed on the ball with strong S intensity in EDX analysis, but after further rubbing, a film with a high concentration of Zn and P was formed.…”
Section: Comparison With Results In Unidirectional Purementioning
confidence: 93%
“…For ZDDP‐containing lubricants derived reaction layers (Figures ), C 1 s signal was originally found at 285.4 eV and 285.5 eV for ester + ZDDP (Figure ) and PAO + ZDDP (Figure ), which were both calibrated to 285.0 eV (CC, CH) and this processing was applied to all the regions and components generated. The second component generated from C 1 s was found at 286.5 ± 0.1 eV for ester + ZDDP and at 286.4 ± 0.1 eV for PAO + ZDDP, which can be referred to COP bond . The third peak from C 1 s was found at 288.8 ± 0.1 eV for both ester + ZDDP and PAO + ZDDP, which can be referred to CS bond …”
Section: Resultsmentioning
confidence: 97%